PENINGKATAN DAYA TAHAN ANAEROBIK LAKTASID ATLET FUTSAL PADA TAHAP PERSIAPAN KHUSUS (TPK) PERIODISASI LATIHAN - budiman abdul jalil, budi (2020)
Periodization is one of the central concepts of training theory, this section describes the process of developing a training plan periodically. Success in a competition or championship is the result of planning, hard work, commitment and training from the athlete. It cannot be denied. planning is a very important tool a trainer can use in trying to direct a well-organized training program. The training program contains a training plan from the start of training to the day of the match, consisting of: general preparation stage (TPU), special preparation stage (TPK), pre-match stage (TPP), main match stage (TPUt) and transition stage. The purpose of this study was to determine the application of an exercise program in the special preparation stage so that it had a significant impact on the increase and anaerobic percentage of lactacids. The method used in this research is an experimental study with a one group pretest-posstest design research design. The sample in this study were 12 athletes of 2019 Sport Science futsal, sampling using non probability sampling techniques. The instrument used is a 150 meter sprint. The results were analyzed using the Wicolxon test on SPSS version 25 to measure the pretest and poststest results that were obtained at the time of the study. As a result, the pretest normality test is 0.042 <0.05 and the posstest is 0.117> 0.05, then the data that has been analyzed using the normality test is not normally distributed. And the hypothesis test shows that the results of the posttest and pretest results are 0.814> 0.05, indicating that there is no significant influence between anaerobic lactacids at the special preparation stage (TPK)